Aplikasi Carbon Nano Fiber Terintegrasi dengan Karbon Aktif Serabut Kelapa untuk Pengolahan Limbah Laundry - Asih Melati (LP2M UIN Sunan Kalijaga, 2017)
The study effect of temperature on the morphology of carbon nanotube (CNF) based coconut husk has been done. CNF is one of the nanotechnology products that can be applied to reduce the concentration of the especially Pb, Cd, Ni. Thepurpose of this study are temperature effect on CNF and determine the potential uses treatment of CNF in the laundry waste. The Growth of CNF used the chemical vapor deposition (CVD) method with a temperature variation of 6000 C,7000 C, and 8000 C. CNF synthesis involves reacting activated carbon from coconut shell, ferrocene (Fe(C5H5)2) as a catalyst, benzene as the carbon source,and argon gas flowed. The Purification of CNF using nitric acid (HNO3) 65%. The result of Energy Dispersive Spestroscopy (EDS) characterization indicate that increasing temperatures indicate increasing carbon content. CNF as adsorbent deposited on the laundry waste. The water quality test of the laundry waste showed that the adsorption of CNF likely reduce Pb level at 67,4% at a temperature of 6000C and DO concentration increases. CNF T has no effect on the amount of PH and Cd, while BOD and COD consentration increases.